P2-S2.13 A pilot study of the effectiveness of a vaginal washing cessation intervention among Kenyan female sex workers. (10th July 2011) - Masese, L; McClelland, R S; Gitau, R; Wanje, G; Shafi, J; Kashonga, F; Ndinya-Achola, J; Richardson, B; Lester, R; Kurth, A
Abstract : Background: Intravaginal practices have been associated with HIV-1 acquisition. This may be mediated by mucosal disruption, changes in vaginal flora, or inflammatory responses in the genital tract. Reducing vaginal washing could lower women's risk of HIV-1 acquisition. We conducted a prospective study to test the hypothesis that a theory-based intervention would reduce vaginal washing in a cohort of high-risk Kenyan women. We collected pilot data on changes in biological markers that might help to explain the relationship between vaginal washing and HIV-1. Methods: HIV-1 seronegative women who reported current vaginal washing were recruited from a prospective cohort study of high-risk women in Mombasa, Kenya. A theoretical framework including Information Motivation and Behaviour and Harm Reduction was implemented to encourage participants to reduce or eliminate vaginal washing. At baseline and after 1 month, we evaluated vaginal epithelial lesions by colposcopy, vaginal flora by Nugent's criteria, and vaginal cytokine milieu using ELISA on cervicovaginal lavage specimens. Results: Twenty-three women were enrolled. The most commonly reported vaginal washing substance was soap and water (N=14, 60.9%). The median frequency of vaginal washing per week was 7 (IQR 0–14). After one week, 21 (91.3%) participants reported cessation of vaginal washing. After 1 month, all participants reported cessation of vaginal washing (p≤0.001 for comparison of baseline to follow-up prevalence). The average number of cervicovaginal epithelial lesions by colposcopy decreased after 1 month compared to baseline (Mean [SD] 0.4 [0.6] vs 0.2 [0.5]; coefficient −0.14; 95% CI −0.29 to 0.01; p=0.08). Although there was no change in the prevalence of BV (OR 1.00, 95% CI 0.42 to 2.38; p=1.00]), these pilot data suggest that the likelihood of detecting Lactobacillus by culture might increase after cessation of vaginal washing (2 [8.8%] vs 6 [26.1%]; OR 3.71, 95% CI 0.73 to 18.76, p=0.11). Most cytokine levels were reduced after cessation of vaginal washing, but in this small, time-limited sample none of these changes were statistically significant. Conclusions: A theory-based intervention was highly successful in reducing vaginal washing over 1 month. This pilot study suggests the need for future studies with a larger sample size and longer follow-up to determine the effects of vaginal washing cessation on the cervicovaginal epithelium, vaginal flora, and inflammatory markers.